Marxistisch-feministisch - Geschichte einer Verbindung im Streit - Haug, Frigga (Österreichische Zeitschrift für Geschichtswissenschaften, 1995)
After positioning the topic in a historical framework, sketching the main paradigm in discussion, the article concentrates on three main areas: 1) the challenge of discussing subjectivity within a marxist tradition which is mainly concentrated on the economic sphere; thus linking the possibility to change society to the necessity of changing oneself. 2) the challenge of criticizing Marx' concept of labour and value-theory and thus bringing domestic labour into the heart of marxism, and connecting the problem with the necessity of reorganizing 'work-society' today. 3) the challenge of linking the critique of political economy to patriarchy and thus doubting the usefulness of thinking domination in a one-dimensional way, and offering a new idea on the fundamental part women's oppression plays in capitalist society. The author summarizes the main discussions from the seventies up to now and links them to her own experiences and contributions in this field. As a feminist she transgresses the boundaries of academic disciplines and covers psychology, sociology, economy and politics.